A comprehensive study on identification of both deck and soffit defects in concrete bridge decks through thermographic investigation of shaded side under natural conditions. (11th October 2021) - Mac, Van Ha; Huh, Jungwon; Doan, Nhu Son; Lee, Bang Yeon; Haldar, Achintya
Highlights: IRT surveys of the shaded side of RC bridge decks were done under field conditions. Defects up to 19.5 cm depth can be detected by IRT alone or combined with PCT. The optimal time of IRT surveys was given to detect both deck and soffit defects. Temperature change and humidity effects on the IRT investigation were indicated. An effective approach was proposed to accurately classify defects in the deck core. Abstract: The present study aims to characterize the suitability of detecting both deck and soffit delaminations in a concrete bridge deck using only a thermographic investigation conducted of the shaded side under natural conditions without and combined with a post-processing method. In addition, the primary contribution and novelty of this study is the classification of delamination as deck or soffit defects by analyzing the behavior of the surface temperature of the bridge deck. Finally, the present work examines not only the weather but also time condition effects related to the identification of both deck and soffit defects under the proposed approach. To fulfill the main aforementioned purposes, this study adopts an experimental approach, wherein two concrete specimens embedded with delaminations are developed and placed on a 4.0-m-high frame, such that their design and the experimental setup reflect the conditions of real concrete bridge decks.